2018
DOI: 10.5114/ms.2018.80951
|View full text |Cite
|
Sign up to set email alerts
|

How does EGFR overexpression affect the development and treatment of rectal cancer?

Abstract: Epidermal growth factor (EGF) stimulates the proliferation of many different types of cells and plays an important role in the formation and growth of tumours. The interaction of EGF with cells is possible by the EGF receptor (EGFR) anchored in the cell membrane. Excess EGFR expression is found in approximately 25-82% of colorectal cancer cases. Attachment of EGF to EGFR results in a conformational change in the receptor, an increase in affinity for neighbouring receptors, receptor dimerisation, and activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The multivariate analysis also showed that high EGFR intensity increases the risk of cancer recurrence 4.3 times (HR = 4.3). Interestingly, our study showed that among patients with high EGFR levels, patients with pT4 predominated ( p = 0.0003), although some researchers say that the correlation between EGFR overexpression and clinical-pathological parameters is not important [ 28 , 30 , 31 ]. According to them, this may seem only an additional molecular event that worsens the result.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The multivariate analysis also showed that high EGFR intensity increases the risk of cancer recurrence 4.3 times (HR = 4.3). Interestingly, our study showed that among patients with high EGFR levels, patients with pT4 predominated ( p = 0.0003), although some researchers say that the correlation between EGFR overexpression and clinical-pathological parameters is not important [ 28 , 30 , 31 ]. According to them, this may seem only an additional molecular event that worsens the result.…”
Section: Discussionmentioning
confidence: 82%
“…Studies to date have not explicitly confirmed the relationship between the EGFR expression and the survival of patients with rectal cancer [26], although the study by Mayer et al showed that the EGFR expression in more than 50% of cancer cells is a negative prognostic factor [27]. Moreover, overexpression of EGFR (upregulation) is associated with more aggressive tumor growth, a poorer prognosis and higher resistance to radiation; therefore it can potentially be a useful marker in predicting complete responses [25,28,29]. The results obtained in our studies confirmed the above-mentioned reportsthe probability of survival was higher in patients with a low EGFR intensity, p = 0.0004.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the evaluation of p21 clinical value, accumulation of this protein in the nucleus is usually described qualitatively, and its presence in tumorous cells was between 36% and 71%, and even up to 80% of the cases. Such discrepancies in the results can be explained mostly by the heterogeneity of clinical material, different methods of determination, and even material archiving [19][20][21][22][23][24]. The most popular method is applied to p21 reaction in relation to its intensity on the intensity scale (4-5 scale).…”
Section: Discussionmentioning
confidence: 99%
“…Although rectal cancer is often mosaic and heterogeneous, we currently have a wide range of tests available, which can be a good way to gain a first insight into the genetic profile [13,14]. An increase in the EGFR expression was observed in tumors of different locations and was usually associated with a poor prognosis, increased risk of relapse and a shorter survival rate [15,16,17]. However, the reports on the effect of the EGFR hyper-expression on survival in rectal cancer are conclusive.…”
Section: Outcomementioning
confidence: 99%